Treat-and-extend regimen of intravitreal aflibercept for type 1 choroidal neovascularisation associated with chronic central serous chorioretinopathy - Король, Андрій Ростиславович; Кустрин, Тарас Богданович; Задорожний, Олег Сергійович; Невська, Алла Олександрівна; Насінник, Ілля Олегович (My University, 2023)
PURPOSE To evaluate the 1-year results of intravitreal aflibercept injections (IVA) using a treat-and-extend (T&E) regimen for type 1 choroidal neovascularisation (CNV) associated with chronic central serous chorioretinopathy (CSC) SETTING / VENUE SI"The Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine" METHODS Participants in this prospective, interventional, single-center clinical study included 22 patients (22 eyes) with CNV in chronic CSC. The primary objective was decimal best-corrected visual acuity (BCVA). The secondary objectives were the intra- and subretinal fluid (ISRF) changes on OCT (complete resolution of ISRF and change in central retinal thickness (CRT)), change in subfoveal choroidal thickness (SFCT) on OCT, interval between the last injection and the final visit, number of intravitreal injections and safety. RESULTS Mean decimal BCVA showed a significant increase from 0.44±0.35 to 0.58±0.3 (P = 0.01) comparing baseline and 1 year. Complete resolution of ISRF was observed in 73% (16 eyes) during observation period. Mean CRT and SFCT decreased significantly from 321±90 to 259±93 µm (P = 0.004) and 364±186 to 287±124 µm (P = 0.0002) respectively, comparing baseline and 1 year. During all follow-up period mean a number of intravitreal injections of aflibercept were 7.5±1.4. Mean interval between the last injection and the final visit was 9.0±4.1 weeks. There were no systemic adverse events and ocular side effects. CONCLUSIONS T&E regimen of intravitreal aflibercept is effectiveness and safe method of treating eyes with type 1 CNV associated with chronic CSC.